Employee Training and Succession Planning of Selected Deposit Money Banks in Abia State, Nigeria - Edeh Ogbu Friday (SEISENSE Journal of Management, 2019)
Purpose- This study investigates the relationship between employee training and succession planning in deposit money banks in Abia State using cross-sectional survey. Ten deposit money banks were surveyed using simple random sampling technique. Design/Methodology- A total population of one hundred and twenty staff was investigated with a sample size of ninety two. Validity of instrument was determined using face validity while Cronbach Alpha was used to ascertain the reliability of the instrument. Spearman’s Rank Order Correlation Coefficient (rho) was used to analyze the hypotheses with the aid of statistical package for social sciences (20.0). Findings- The study found that employee training has a positive significant relationship with succession planning. It concluded that employee training measured in terms of on-the-job training and mentoring promotes succession planning in deposit money banks. Practical Implications- The study recommends that managers, human resource professionals as well as directors of financial institutions should employ on-the-job training and mentoring for effective succession planning in the workplace.